An Extensive Survey On Resource Allocation Mechanisms In Cloud Computing - Jansi Sophia Mary C, Dr. Mahalakshmi K (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
At present scenario, Cloud Computing is the emerging trend technology in order to store, process, visualize and analyze data in an efficient way. It deals with on demand dynamic resource allocation for giving assured services to the consumers. Pay-As-You-Use model is used here to the public. Resource Allocation is carried out beside with intention of reducing the price associated with it. In recent days, the major functions of Resource Allocation are meeting the needs of customers and application requirements. Different resource allocation techniques had been inspected in this paper.